Method of arranging correspondence records in village offices in Jatilawang District, Banyumas Regency - Anwar Mustofa; Supriatnoko Supriatnoko; Mawarta Onida; Ni Made Widhi Sugianingsih (Interdisciplinary Social Studies, 2024)
This study aims to determine the kinds of correspondence records that are managed by village offices, how to store them, how to handle them, and the means used to store them so that the records retrieval is easy so as allowing the data contained in the records as a source of information. Through surveys and observations, the research took place in all village offices in Jatilawang sub-district, Banyumas district, Central Java province. From the results of the survey and observation, the researchers concluded that there are differences from one village office to another in the management of correspondence records. However, there are similarities in the handling of the correspondence records, namely every incoming letter and outgoing letter are recorded first in the agenda book, the village head knows every incoming and outgoing letters because every letter received by the office should be transferred first to the Village Head to be assigned to a certain village staff to execute the purpose of the letter. All records are principally managed by Kaur (kepala Urusan) or staff for mail handling and administration affairs, but Kaur or staff for Kesejahteraan or welfare affairs and Kepala Dusun or staff for human empowerment still retain some correspondence records. Some of the differences in the handling of the correspondence records, namely in the format agenda book, the means used to manage the records, and records arrangement method.